In vitro cytotoxic effect of annona squamosa pulp ex-tract as a mouthwash for children on human normal cell line - Ali , Sumaia Hussein; Jafar , Zainab Juma (Journal of Baghdad College of Dentistry, 2022)
Background: Fruits and their by-products are the primary sources of bioactive chemicals in plants. Because of its phytochemical richness, Annona squamosa fruits have gained the alertness of people willing in health-promoting diets. The purpose of this in vitro study was to evaluate the cytocompatibility effect of ethanolic crude extract of Annona squamosa pulp against a human normal cell line as a mouthwash for children. Material and method: The ethanolic extract of Annona squamosa pulp was extracted using the ultrasonic method and then lyophilized to make it powder. The MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) test was performed to investigate the cytotoxic activity of the pulp extract on a human normal cell line derived from human dermal fibroblast, neonatal (HDFn). Plates were then incubated with 5% CO2 at 37°C For the following concentrations (400, 200, 100, 50, 25, 12.5, 6.25 g/ml). Each concentration, as well as the positive control chlorhexidine, and the negative control cells without tested material, were tested in triplicate. Results: No significant difference was found between the cytotoxicity of the ethanol crude extract of Annona squamosa and a chlorhexidine (P = >0.05) against human dermal fibroblast of neonate cells, with IC50 (50% growth inhibition of cells) values of 235.4 μg/mL while chlorhexidine had an IC50 of 97.8 μg/mL. Conclusion: Annona squamosa extract is more safe and has less cytotoxicity than chlorhexidine. So, to overcome the problems of chlorhexidine, herbal mouthwash formulations could be utilized as an al-ternative mouthwash.